Penciptaan Drama Musikal Sweeney Todd: The Demon Barber of Fleet Street (Sweeney Todd:Tukang Cukur Haus Darah) - Husni Wardhana; Suharyoso Suharyoso (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2011)
Proses kreatif penyutradaraan Sweeney Todd: The Demon Barber of Fleet Street memberi banyak pelajarantentang drama musikal. Drama musikal memiliki keunikan tersendiri dalam proses maupun bentuk penyajiannya.Jenis drama ini sangat populer di Amerika, dan merupakan satu-satunya sumbangan Amerika dalam memperkayajenis teater dunia. Cerita ini merupakan kisah legendaris Inggris. Berkali-kali naskah karya Christopher Bond inidimainkan di berbagai benua di dunia, namun bila dilihat dari sejarah penciptaannya, kisah balas dendam seorangtukang cukur ini telah melalui proses adaptasi yang panjang. Beberapa penulis besar di jamannya sebelum melewatitangan kreatif Christopher Bond telah mengkreasi ulang naskah ini. Drama musikal ini berawal dari komedi musikaldan sejak tahun 1920 mengangkat tema-tema serius yang biasa disebut musik Broadway atau musik Amerika. Biasadisajikan dalam panggung besar West End dan Broadway di London, New York, Australia dan Asia. Beberapa kalidipanggungkan oleh kelompok teater sekolah atau kelompok teater amatir. Hampir seluruh pertunjukan drama musikal Sweeney Todd: The Demon Barber of Fleet Street diiringi dengan musik dan dinyanyikan. Dialog diubahmenjadi nyanyian. Para aktor di tuntut untuk dapat menyanyi, akting, dan menari. Drama musikal merupakanpertunjukan yang menggunakan tiga ciri utama, yakni menyanyi, menari, dan berakting yang mendominasi hampirseluruh pertunjukan.Kata kunci: penyutradaraan, drama musikal, kisah legendaris, Sweeney Todd, teater sekolah.ABSTRACTThe musical drama Sweeney Todd: Th e Demon Barber of Fleet Street. The creative directing process of this drama has given many good lessons to the art work of performing arts, especially to musical drama performance. The musical drama has its own unique characteristics in its process and performance. This type of drama is very popular in the USA, and has been the only contribution from the USA to enrich the typical of world theater. Sweeney Todd: The Demon Barber of Fleet Street is as an English legend, especially in England. This script created by Christopher Bond has been performed for several times in all around the globe. Having seen from its creating history, the story of a barber who takes revenge has been through long adaptation process. Some big authors in this era, before proceeded by Christopher Bond’s creative touch, had creatively recreated this script. The musical drama Sweeney Todd: The Demon Barber of Fleet Street was fi rstly created from the musical comedy drama and since 1920 has shown serious themes that are well known as Broadway music or American music. This drama has commonly been shown on a big stage West End and Broadway in London and New York, also in Australia and Asia. Moreover, it has also been performed by groups of school-theater and amateur theater. Most of the musical drama performances Sweeney Todd: The Demon Barber of Fleet Street are accompanied by music and are sung as well. The dialog is changed into songs. The actors are supposed to be able to sing, to act, and to dance. The musical drama is a performance that uses three main characteristics, namely: singing (solo, ensemble, and choir), dancing (individual and group), and acting, that dominates in most parts of the performance.Key words: directing, musical drama, legend story, Sweeney Todd, theater.